Recent Advances in the Utilization of Chiral Covalent Organic Frameworks for Asymmetric Photocatalysis - Peng Liu; Weijun Dai; Xianfu Shen; Xiang Shen; Yuxiang Zhao; Jian-Jun Liu (Molecules)
The use of light energy to drive asymmetric organic transformations to produce high-value-added organic compounds is attracting increasing interest as a sustainable strategy for solving environmental problems and addressing the energy crisis. Chiral covalent organic frameworks (COFs), as porous crystalline chiral materials, have become an important platform on which to explore new chiral photocatalytic materials due to their precise tunability, chiral structure, and function. This review highlights recent research progress on chiral COFs and their crystalline composites, evaluating their application as catalysts in asymmetric photocatalytic organic transformations in terms of their structure. Finally, the limitations and challenges of chiral COFs in asymmetric photocatalysis are discussed, with future opportunities for research being identified.